Integrating 3D Flower-Like Hierarchical Cu2NiSnS4 with Reduced Graphene Oxide as Advanced Anode Materials for Na-Ion Batteries - Yuan, Shuang; Wang, Sai; Li, Lin; Zhu, Yun-hai; Zhang, Xin-bo; Yan, Jun-min (ACS applied materials & interfaces, 2016)
Development of an anode material with high performance and low cost is crucial for implementation of next-generation Na-ion batteries (NIBs) electrode, which is proposed to meet the challenges of large scale renewable energy storage. Metal chalcogenides are considered as promising anode materials for NIBs due to their high theoretical capacity, low cost, and abundant sources. Unfortunately, their practical application in NIBs is still hindered because of low conductivity and morphological collapse caused by their volume expansion and shrinkage during Na+ intercalation/deintercalation. To solve the daunting challenges, herein, we fabricated novel three-dimensional (3D) Cu2NiSnS4 nanoflowers (CNTSNs) as a proof-of-concept experiment using a facile and low-cost method. Furthermore, homogeneous integration with reduced graphene oxide nanosheets (RGNs) endows intrinsically insulated CNTSNs with superior electrochemical performances, including high specific capacity (up to 837 mAh g–1), good rate capability, and long cycling stability, which could be attributed to the unique 3D hierarchical structure providing fast ion diffusion pathway and high contact area at the electrode/electrolyte interface.